ETIKA PESERTA DIDIK PERSPEKTIF KH. HASYIM ASY’ARI - Mohamad Solihin (STIT Islamic Village Tangerang, 2022)
As Caliph (khalifah) in this earth, human beings are not only entrusted to keep, take care, and maintain the prosperity of this nature but also required to be just in all affairs. The establishment of this noble morals and ethics is supposed to be the goal of education. However, what happens nowadays is the opposite, the crisis of education and the lack of attention to the morals and ethics in education. Actually, ethical aspect in Islamic education is not a taboo thing, because it has been widely expressed by experts such as al-Ghazali, Ibn Miskawaih, Syaikh al-Zarnuji, and so forth. Therefore, the writer is interested to rediscover the educational thought of K.H Hasyim Asy’ari in his book, Adab al-Alimwaal-Muta'alim, under the sub-focus of KH. Hasyim Asy’ari’s view on the ethics of Islamic education and the concept of learner’s ethics.This research was conducted by using library research with descriptive qualitative approach. The data collection is performed by collecting the existing data through books, documents, magazines and the internet (website).The data were thenanalyzed so that the researchers could find the concluding ideason the subject studied. Data were analyzed using induction, deduction and comparison approach. This research concluded that according to KH. Hasyim Asy'ari, learners should be knowledgeable and true. It means to have an attitude which suits the principles or values of education in Islam. The more specific concept to be performed is the way to behave to themselves, teachers, the lessons and books. In this sense, KH. Hasyim Asy’ari does not mention the specific lessons to be given in accordance with the talents, interests, and abilities of the learners.